2009
DOI: 10.1088/0964-1726/18/5/055010
|View full text |Cite
|
Sign up to set email alerts
|

A carbon nanotube/cement composite with piezoresistive properties

Abstract: This paper studies the piezoresistive property of the CNT/cement composite to explore its feasibility as an embedded stress sensor for civil structures such as roadways, levees and bridges. The experimental results show that the electrical resistance of the CNT/cement composite changes with the compressive stress level, indicating the potential of using the CNT/cement composite as a stress sensor for civil structures. The piezoresistive responses of the composite with different fabrication methods and CNT dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
131
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(140 citation statements)
references
References 23 publications
4
131
2
3
Order By: Relevance
“…Damage or stain affects the bulk conductivity to decrease, as reported for damage in the elastic regime [29], plastic (inelastic) deformation region [30,31] and after complete fracture [30]. Other researchers used carbon nanotubes instead of carbon fibre in cement for strain sensing applications and reported electrical conductivities decreasing upon tension [23] and increasing upon compression [24][25][26][27]. Luo et al prepared hybrid cement composites using carbon whiskers and carbon nanotubes and reported superior sensing than the use of carbon nanotube as the sole conductive admixture [28].…”
Section: Structural Health Monitoring (Shm) Is a Type Of A Non-destrumentioning
confidence: 96%
See 1 more Smart Citation
“…Damage or stain affects the bulk conductivity to decrease, as reported for damage in the elastic regime [29], plastic (inelastic) deformation region [30,31] and after complete fracture [30]. Other researchers used carbon nanotubes instead of carbon fibre in cement for strain sensing applications and reported electrical conductivities decreasing upon tension [23] and increasing upon compression [24][25][26][27]. Luo et al prepared hybrid cement composites using carbon whiskers and carbon nanotubes and reported superior sensing than the use of carbon nanotube as the sole conductive admixture [28].…”
Section: Structural Health Monitoring (Shm) Is a Type Of A Non-destrumentioning
confidence: 96%
“…Classifying cement as ceramics, damage sensing has been achieved in various studies with the incorporation of short carbon whiskers [20][21][22]. For cement composites with conductive fillers, self-sensing is made attainable by the damage and/or strain on the volume electrical conductivity of damaged or strained material [20][21][22][23][24][25][26][27][28]. Damage or stain affects the bulk conductivity to decrease, as reported for damage in the elastic regime [29], plastic (inelastic) deformation region [30,31] and after complete fracture [30].…”
Section: Structural Health Monitoring (Shm) Is a Type Of A Non-destrumentioning
confidence: 99%
“…Experimental results conducted by Yu and Kwon 12 showed that the electrical resistance of cementitious composites manufactured with CNT changed when a stress field was applied, thus indicating a significant potential as stress/strain sensors for civil engineering structures. The use of a chemical additive provided a homogeneous dispersion of CNT into the cement paste, which can however affect the characteristics of the piezoresistive composite.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a chemical additive provided a homogeneous dispersion of CNT into the cement paste, which can however affect the characteristics of the piezoresistive composite. A higher level of CNTs dispersed in the composite may increase the sensitivity of the material as a piezoelectric sensor 12 . When adding epoxy resin into the cement paste, one can obtain in principle a material with interesting mechanical characteristics from a structural engineering perspective (low density, high toughness and strength).…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured carbon embedded systems have proven to be more sensitive towards structural damage [10][11][12][13][14][15][16]. Most of the previous researched methods incorporating CNTs were based on the sensing of damage of long-fibre or woven reinforced epoxy [10][11][12][13][14][15][16] or for other brittle matrices like cement for civil structures [19]. Such studies aimed to induce damage systematically to the nanocomposite sample using tensile [10,11] and bending [11,12] modes.…”
mentioning
confidence: 99%